CONSEQUENCES OF THE QUALITY OF FINANCIAL REPORTING - Abdul Nesser Hasibuan (CV. Radja Publika, 2024)
This study investigates the economic consequences of the quality of financial reporting in the manufacturing industry of the Indonesian Stock Exchange (Bursa Efek Indonesia). The sample comprises 100 manufacturing companies listed on the Indonesian Stock Exchange, observed over a period of 5 years. The analysis employs Structural Equation Modeling (SEM). The findings indicate that the financial performance characteristics do not significantly affect the quality of market-based financial reporting. However, these characteristics do have a significant impact on the quality of accounting-based financial reporting. Moreover, the intervening variables, represented by the influence of the company's performance on market-based and accounting-based financial reporting, exhibit a significant effect, which is notably larger than the direct impact. These results highlight the intricate relationship between financial performance, the quality of financial reporting, and their economic consequences within the manufacturing sector of the Indonesian Stock Exchange. They underscore the importance of accounting practices and reporting quality in shaping investors' perceptions and decision-making processes, thereby impacting the overall economic outcomes of the companies involved.